Novel approaches for integrated grain storage management. Issue 1 (2nd January 2016) - Kostyukovsky, Moshe; Trostanetsky, Anatoly; Quinn, Elazar
ABSTRACT: The solution of the global food crisis and improvement of the food security situation may be reached by increasing food production and prevention of losses during the food supplying chain. Most of the scientific efforts so far have aimed to increase the yield of agricultural crops. However, food losses during storage and the supply chain may reach levels of 20–40%. One of the most significant factors responsible for the global food crisis is grain losses during storage that are largely caused by pest insects. Today, there are two main chemical methods used for stored product insect pest control: fumigation and grain protection by contact insecticides. For both these methods phyto-sanitarian, health, and ecological disadvantages are well documented. Therefore, the global current tendency is to prevent/decrease the common wide use of chemical insecticides with high toxicity to humans for pest control in foods. Thus, there is an urgent need for the development of alternative eco-friendly approaches for insect pest control in order to prevent grain quantity losses and the quality degradation of stored grain and dry food caused by insect pests. In this article, we propose an integrated protection approach which includes prevention measures, systematic inspection and monitoring for grain storage risk factors; use of eco-friendly protectants and volatiles; and improved technologies for currently used fumigants. Implementation of this approach in Israel resulted in a dramatic reduction in grain losses to less than 0.5%.